2002
DOI: 10.1207/s15327752jpa7801_04
|View full text |Cite
|
Sign up to set email alerts
|

A Process Dissociation Approach to Objective-Projective Test Score Interrelationships

Abstract: Even when self-report and projective measures of a given trait or motive both predict theoretically related features of behavior, scores on the 2 tests correlate modestly with each other. This article describes a process dissociation framework for personality assessment, derived from research on implicit memory and learning, which can resolve these ostensibly conflicting results. Research on interpersonal dependency is used to illustrate 3 key steps in the process dissociation approach: (a) converging behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 110 publications
6
124
1
7
Order By: Relevance
“…Thus, the lo w correlation of scores for d ifferent measures for evaluating the same construct does not necessarily mean a problem of incremental valid ity. Th is is because somet imes the lack of weak co rrelat ion o r lo w magnitude is evidence to support the valid ity of pro ject ive techniques, demonstrating its clinical and empirical usefulness for certain constructs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the lo w correlation of scores for d ifferent measures for evaluating the same construct does not necessarily mean a problem of incremental valid ity. Th is is because somet imes the lack of weak co rrelat ion o r lo w magnitude is evidence to support the valid ity of pro ject ive techniques, demonstrating its clinical and empirical usefulness for certain constructs [11].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was quite surprising considering the advantages stated in the literature about using implicit and explicit cognitions to capture personality and predict behaviors Bornstein, 2002;Winter et al, 1998). However, the literature also states that due to low power for detecting interactions, researchers should consider increasing power by setting critical alpha at .10 for the interaction term in MHMR analyses (Cohen, 1988;Champoux & Peters, 1980;Finn & Frone, 2004;McClelland & Judd, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…There is significant difference between implicit and explicit cognitions (Bornstein, 2002;Brewin, 1989;Epstein, 1994;Fazio & Olson, 2003;Greenwald & Banaji, 1995;Hogan, 1991;James, 1998;LeBreton, Binning, & Adorno, 2006;McClelland et al, 1989;Mischel & Shoda, 1995;Spangler, 1992;Westen, 1998;Winter et al, 1998). Specifically, as McClelland and colleagues (McClelland, 1985;McClelland et al, 1989) found, when implicit and explicit personality cognitions are measured they are often uncorrelated and are likely to interact when predicting various criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations